Predicting mental motivation in terms of some artistic gymnastics skills for students of the College of Physical Education and Sports Sciences - م.م علا سلام غازي; أ.د. هدى عبد السميع (الرياضة المعاصرة, 2021)
The importance of the research lies in trying to identify these variables and to know the relationship between mental motivation and the performance of some artistic gymnastics skills for students of the College of Physical Education and Sports Sciences. The problem of the research is that learning skills in any game or activity does not depend only on the physical and technical side, but the psychological aspect has a great role. In her learning, and with this, the researchers noticed that the educational process depends mainly on physical, technical and psychological interdependence, and through the researchers' experience of being specialized in and informing her of these lessons, they found that the psychological aspect is not included in the educational units used in the curriculum for most of the professor in the Faculties of Physical Education and Sports Sciences in Iraq Which reflects negatively on the preparation of students from the psychological side, especially in the variable of mental motivation that must be characterized by each student. One of the aims of the research is to identify the mental motivation and performance of some artistic gymnastics skills for students of the College of Physical Education and Sports Sciences.